2020
DOI: 10.3390/plants9050603
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on the Role of Allyl Isothiocyanate in Controlling the Root Knot Nematode Meloidogyne hapla

Abstract: Biofumigation, although a well-known method, is still controversially debated as a management strategy for plant-parasitic nematodes (PPN). Its controlling effect is attributed to the production of isothiocyanates (ITCs) following the action of myrosinase on glucosinolates (GSLs). Different ITCs are formed from different GSLs, depending on the plant species. To better understand the potential of ITCs, eight cultivars from three Brassicaceae species were investigated as biofumigation crops to control the root k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…ITCs are highly toxic, leading to a suppressive effect of Brassica species on soil-borne pathogens and herbivores [ 36 ]. Therefore, Brassica species including B. juncea are used as cover crops in PPN management via so-called bio-fumigation [ 37 , 38 ]. Nevertheless, B. juncea is a host of M. incognita [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…ITCs are highly toxic, leading to a suppressive effect of Brassica species on soil-borne pathogens and herbivores [ 36 ]. Therefore, Brassica species including B. juncea are used as cover crops in PPN management via so-called bio-fumigation [ 37 , 38 ]. Nevertheless, B. juncea is a host of M. incognita [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…As soil can have a crucial effect on nematicidal activity [ 6 , 14 ], the controlling effect of NEMguard ® DE against M. incognita was further tested in small pots using silver sand:soil mixture. Our results revealed that the single application of NEMguard ® DE, as recommended by the supplier [ 14 ], reduced root galling on tomato plants, 31 days after M. incognita inoculation ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although most chemical nematicides show high nematicidal efficacy under field conditions, their impact on human health and on the environment has resulted in enforced regulation or the total ban of the different products [ 3 ]. To control plant-parasitic nematodes, grafting, biofumigation, heat treatment, soil compost and crop rotation with poor hosts, catch crops or antagonistic microorganisms have been intensively studied [ 4 , 5 , 6 ]. However, further management methods, such as plant-based metabolites are being investigated to search for alternative human and environment friendly biopesticides [ 3 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lower values of all these parameters suggest better interactions. observation was made by Dahlin and Hallmann (2020) during an in vitro bioassay of various isocyanates against M. hapla, where the significant recovery of isocyanate-treated J 2 s from inactive states was observed at a lower concentration. The same study reported that the J 2 s exposed to a low concentration of AITC, after recovery, were still able to cause root galling in cucumbers.…”
Section: Discussionmentioning
confidence: 99%